2011
DOI: 10.1111/j.1538-7836.2011.04509.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protein disulfide isomerase regulates feedback activation of platelet thrombin generation via modulation of coagulation factor binding

Abstract: To cite this article: Jurk K, Lahav J, Van Aken H, Brodde MF, Nofer JR, Kehrel BE. Extracellular protein disulfide isomerase regulates feedback activation of platelet thrombin generation via modulation of coagulation factor binding. J Thromb Haemost 2011; 9: 2278-90.Summary. Background: Protein disulfide isomerase (PDI) controls platelet integrin function, tissue-factor (TF) activation, and concentrates at fibrin and thrombus formation sites of vascular injury. Objective: To investigate the involvement of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 47 publications
4
73
1
1
Order By: Relevance
“…This finding is consistent with previous studies in which authors used the same assay and reported that the majority of surface reductase activity on nonstimulated platelets was attributable to PDI. 42,43 However, ERp57 surface reductase activity increased dramatically with thrombininduced platelet activation ( Figure 7C), with ERp57 now contributing the large majority (83%) of the disulfide reductase activity on activated platelets. The large increase of platelet surface reductase activity with platelet activation attributable to ERp57 indicates that active sites of the enzyme are in the free thiol form required to cleave the S-S bond in GSSG, the form of the active sites that also catalyze thiol-disulfide exchange reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies in which authors used the same assay and reported that the majority of surface reductase activity on nonstimulated platelets was attributable to PDI. 42,43 However, ERp57 surface reductase activity increased dramatically with thrombininduced platelet activation ( Figure 7C), with ERp57 now contributing the large majority (83%) of the disulfide reductase activity on activated platelets. The large increase of platelet surface reductase activity with platelet activation attributable to ERp57 indicates that active sites of the enzyme are in the free thiol form required to cleave the S-S bond in GSSG, the form of the active sites that also catalyze thiol-disulfide exchange reactions.…”
Section: Discussionmentioning
confidence: 99%
“…On the platelet surface, PDI is implicated in integrin activation, and mediates platelet adhesion, aggregation, granule secretion as well as thrombin formation on the platelet surface. [27][28][29][39][40][41] 30,42 Like PDI, ERp5 and ERp57 are involved in platelet aggregation, integrin activation, and degranulation. 30,43,44 Various molecules are known, which bind to PDI and inhibit its thiol isomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the potential anticoagulant activity of PDI inhibition in humans, we measured thrombin generation in a coagulation assay dependent on PDI activity on the thrombin-platelet amplification loop (31). Following oral administration of isoquercetin, platelet-dependent thrombin generation in plasma decreased significantly in both the healthy cohort as well as in individuals with anti-phospholipid antibodies.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%